One river, one planning, and one integrated management policy for flood-free - Rahmat Salam; Izzatusolekha; Tria Patrianti; Muhammad Iqbal; Fithria Sari Andalas; Ardan Syukur (Jurnal Konseling dan Pendidikan, 2025)
Greater Jakarta, a densely populated metropolitan area, continues to face persistent and complex flooding challenges. Despite flood control efforts in the environmental sector, these initiatives remain fragmented and lack integration. This research aims to integrate river management policies to reduce flood risks in Greater Jakarta, a critical economic region. By developing a cohesive approach, the study seeks to formulate effective mitigation strategies focused on sustainable river management planning, enhanced coordination among stakeholders, and the development of adaptive flood management solutions. The research proposes an innovative model for integrated flood management under the concept of "One River, One Planning, One Integrated Management," which addresses the fragmentation of river management through a holistic approach. This model incorporates key aspects such as groundwater resources, sanitation, and agricultural irrigation. The study employs an Explanatory Sequential Design methodology, integrating quantitative and qualitative data analysis in two stages. In the first stage, quantitative data were collected through surveys with 350 respondents from seven areas in Greater Jakarta, representing diverse community demographics. In the second stage, qualitative data were gathered through interviews with seven heads of the Environmental Agency (DLH) across these regions, as well as group discussions with 25 representatives from government, academia, and Watershed Forums. The research utilizes multiple indicators to assess the effectiveness of the proposed policy model, including technical infrastructure, stakeholder coordination, and community participation. The findings suggest that integrated flood management strategies can enhance collaboration among stakeholders, improve flood mitigation practices, and strengthen the capacity of the River Authority Agency (BOS) in Greater Jakarta. Statistical results and qualitative insights from the study highlight the potential for policy innovation, particularly in fostering inter-agency collaboration. The research’s main outputs include a Sinta 2 Journal article, policy briefs, intellectual property rights (IPR), and proposals to the government for strengthening flood management frameworks. The study demonstrates practical contributions to flood management, providing actionable insights for improving policy implementation and coordination across multiple governance levels.